Willow short rotation coppice. Energy and environmental assessment - Stelian Alexandru Borz; Salvatore Papandrea; Michele Zoli; Jacopo Bacenetti; Andrea Rosario Proto (Cleaner Environmental Systems)
Wood chip production from short-rotation coppice (SRC) can be an interesting opportunity for farmers and for the environment. SRC cultivation in fertile arable land, with full mechanisation of the operations, results in higher yields. However, the establishment of SRC is more rational in marginal areas where the conventional crops cannot provide suitable results. In this context, the mechanisation of SRC plays a relevant role, and the availability of small machinery is a key element.In this study, two different willow SRC management regimes, characterised by the adoption of small mechanisation solutions for crop management and harvesting, were compared. The life cycle assessment (LCA) was applied considering 1 cubic metre of wood chips as the functional unit (FU) and a ‘from cradle to gate’ perspective regarding the system boundary. Primary data were directly collected via field trials and interviews with the farmers.The results highlighted how the mechanisation of different field operations is the main cause of environmental impact, which is primarily due to the felling and chipping of stems. The 3-year SRC harvesting regime, despite lower productivity, presents better environmental performance compared to the 2-year one for all the evaluated impact categories, owing to a reduction of the environmental impact related to harvesting.